Relação Professor/a-Aluno/a: contribuições para o processo de desenvolvimento e aprendizagem - SOUZA, Andressa Rafaela da Silva (2023)
The present research entitled “Teacher/Student Relationship: Contributions to the Development and Learning” has the general objective of reflecting the relevance of this socialization and its contribution to the development and learning of the child in the classroom of class. From this perspective, it is necessary to question how the teacher's performance can be significant for this event and what the relevant aspects underlie this relationship. For the development of this work, a bibliographic research was used and the theoretical framework that supported its development is based on studies of authors such as Freire (1996), Galvão (1995), Mizukami (1986), Libanêo (1990), Gadotti (1996) between others. It also used a field research that took place in a school from the municipality of Concórdia do Pará in a class of 1st year of elementary school and the methodological course was based on a qualitative approach where data collection necessary was through a participatory observation and an interview. As As a result, the research points out that having the classroom as a space for interaction and construction of knowledge with its particularities, it is understood that the teacher/student relationship is effective and significant when guided by dialogue, affection and discipline. We must consider this relationship as an essential condition for learning, because knowledge necessary for the growth of all subjects involved in the educational process arise from it.